Perception On Potential Of Zakat Fund In Muslim Society In Bangkok, Thailand - Sitisan, Ekarat Sitisan (2010)
Despite the zakat payment is an individual basis as stated in al-Quran and al- Hadith, it should be managed systematically in accordance with its traits which beyond a personal religious worship. For this reason, the institution which manages the zakat affairs is considered as a social institution that plays an important role in the development of social and economic well-being. Not only happened to Muslims countries but also to non-Muslims countries, such as Thailand. Behind the development of zakat in Thailand, there is an interesting matter happened in Bangkok which is the capital of Thailand and dominated by non-Muslims. Although the zakat funds are available in Bangkok, the lack of data related to them is very much conceded. This condition is probably caused by a number of weaknesses that need to be proved. At least, there are five questions to be treated in order to perceive the zakat fund in Bangkok. First, what is actually happen to the current zakat funds management in Bangkok? Second, what is hovering in the mind of the Muslims community in Bangkok towards zakat funds? Third, what is the potential of zakat funds in Bangkok? Fourth, what is the management problem of zakat in Bangkok? Fifth, how to overcome the problems identified? These five questions lead to the objectives of this study which aim to (1) assess the current zakat management practiced in Bangkok amongst Muslims communities, (2) analyse the perception of potential of zakat funds in Bangkok.